Addressing mental health and reemployment for unemployed Australians through psychological interventions: An applied study. (October 2013) - Henderson, Kylie A; Muller, Juanita J; Helmes, Edward
Few studies have examined the effectiveness of interventions to improve mental health in the unemployed. Current evidence points to interventions improving mental health but having little, if any, impact on reemployment. In the Australian context, psychological services continue to be delivered yet little is known about their effectiveness. This study examined the effectiveness of psychological services for 783 unemployed individuals. It was hypothesized that psychological intervention would improve the symptoms of depression, anxiety, stress and general psychological distress; that individual one-on-one interventions would be more effective than other interventions; and that improvements in mental health would be associated with reemployment. Results highlighted that psychological intervention was effective at improving mental health; that tailored individual interventions were not significantly more effective than other types of interventions and that improvements in depression, anxiety and stress were associated with reemployment.